2003
DOI: 10.1034/j.1600-6143.2003.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Costimulatory Molecule Gene Polymorphisms on Clinical Outcomes in Liver Transplantation

Abstract: CTLA-4 and CD28 deliver opposing signals for T-cell proliferation. We examined single nucleotide polymorphisms (SNPs) CTLA-4 -318C/T and CD28 IVS3 +17T/C for associations with acute rejection in liver transplant recipients. These and two other polymorphisms in CTLA-4 [microsatellite polymorphism +642(AT) n and SNP +49 A/G] were also analyzed for influence on graft survival. Two hundred and eleven liver transplant recipient genotypes were determined by direct sequencing or restriction fragment length polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 43 publications
1
17
2
Order By: Relevance
“…On the other hand, such results were not reported in colorectal cancer [40,41]. The opposite results were obtained in the majority of studies devoted to autoimmunological disorders, in which the CTLA-4c.49AϾG [G] allele was associated with susceptibility to disease [13,30,42,43].…”
Section: Discussioncontrasting
confidence: 56%
“…On the other hand, such results were not reported in colorectal cancer [40,41]. The opposite results were obtained in the majority of studies devoted to autoimmunological disorders, in which the CTLA-4c.49AϾG [G] allele was associated with susceptibility to disease [13,30,42,43].…”
Section: Discussioncontrasting
confidence: 56%
“…Marder et al studied the association of CTLA4 318, 49 and CD28 gene polymorphisms with liver transplant outcomes. Although no significant differences were observed between CTLA4 318 and CD28, significant differences between CTLA4 49 and liver transplant outcomes were detected (Marder et al, 2003b). In a previous study, we reported that there is a significant association between IFN-γ, IL-6 polymorphism liver, and kidney transplant outcome (Karimi et al, 2011(Karimi et al, , 2012.…”
Section: Haplotype 3 Ctacgacggcmentioning
confidence: 92%
“…In animal models, preventing CD28, CD80, and CD86 co-stimulation by targeted deletion or treating monoclonal antibodies against these receptors, could significantly improve allograft outcomes (Marder et al, 2003b). Also, several studies have evidenced the role of CTLA4-Ig as a promoter of graft survival (Sayegh and Turka, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…However, because CD28, CTLA4,and ICOS loci are in close proximity, possible linkage disequilibrium (LD) between the alleles of these genes should be taken into account. Another important point to consider in these association studies is the ethnic homogeneity of the groups being compared because differences in allelic frequencies have been observed among different ethnic groups [5,6].…”
Section: Introductionmentioning
confidence: 99%